EXPLORING THE NURSING-PHYSICIAN COMMUNICATION IN INTENSIVE CARE UNITS. - Faisal Dakeel Mohammed Aljohani, Nazih Khalil Ghalfan Kamili, Alaa Hamad Jarallah Alsahli, Tahani Owyied Hamed Alnezi, Jamila Abdualrahman Almotairi, Aljoharah Zaid Binnamshan, Nasser Sanad Alsanani, Khalid Abdullah Mohammad Alshammari; Mashael Ali Jeadi, Ashwaq Mohammed Tayran, Abdulrahman Ibrahim Suhail, Fahed Halaf A. Aldhafeerl, Abdulaziz Al-hamidi Shadeed Al-harbi, Talal Al-hamidi, Shadeed Al-harbi, Mansour Zakir Al-harbi, Aisha Musa Mubark (Chelonian Research Foundation, 2022)
Ensuring high-quality patient care and safety in healthcare settings requires effective communication between nurses and doctors. Nevertheless, intrinsic variations in communication styles, role views, and practice contexts make it difficult to achieve good communication. The effectiveness and significance of interventions targeted at enhancing nurse-physician communication are examined in this review. Even while initiatives like the SBAR framework have shown promise in standardizing communication, further research is needed to ensure that they are widely applicable. Technology, like electronic medical records, hasn't always made communication better, and further approaches could be needed to increase efficacy. Compared to nurses, doctors tend to view communication interventions more favorably, which emphasizes the significance of addressing different viewpoints to foster understanding and cooperation. One strategy that has shown promise for promoting in-person meetings and strengthening the professional ties between nurses and physicians is the localization of physicians to individual units. Careful thought should be given to how feasible and scalable these interventions would be in a variety of healthcare environments. Future initiatives to enhance physician-nurse communication should give priority to all-encompassing strategies that consider the viewpoints of both professions. In order to foster a collaborative healthcare environment that promotes effective communication and the best possible patient care, it can be helpful to combine technology with interpersonal tactics. It's critical to address obstacles like language and cultural barriers in order to improve communication efficacy and encourage favorable patient outcomes.